2015
DOI: 10.1155/2015/480842
|View full text |Cite
|
Sign up to set email alerts
|

Association between Portal Vein Thrombosis and Survival in Non-Liver-Transplant Patients with Liver Cirrhosis: A Systematic Review of the Literature

Abstract: A systematic review of the literature was performed to analyze the association between portal vein thrombosis (PVT) and survival in non-liver-transplant patients with liver cirrhosis. PubMed, EMBASE, and Cochrane Library databases were searched for all relevant papers which evaluated the prognostic value of PVT in predicting the survival of liver cirrhosis. Meta-analyses were not conducted because the ways of data expression and lengths of follow-up were heterogeneous among studies. Overall, 13 papers were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
3
21
0
3
Order By: Relevance
“…Acute PVT in 70% of patients was improved after TIPS treatment, which is consistent with previous studies that PVT disappearance occurred in 57% to 100% of patients[ 22 , 24 ]. We consider that this is consistent with the view that a reduced portal vein flow velocity is the key risk factor for PVT formation[ 7 , 14 , 25 ]. Patients with concomitant cirrhosis have significantly slower portal vein flow rates than the healthy population[ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…Acute PVT in 70% of patients was improved after TIPS treatment, which is consistent with previous studies that PVT disappearance occurred in 57% to 100% of patients[ 22 , 24 ]. We consider that this is consistent with the view that a reduced portal vein flow velocity is the key risk factor for PVT formation[ 7 , 14 , 25 ]. Patients with concomitant cirrhosis have significantly slower portal vein flow rates than the healthy population[ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, previous studies also reported that the presence of PVT might be associated with the long-term mortality (3 years) in nonliver transplant patients with cirrhosis, but not with the short-term mortality (5 days, 6 weeks, and 1 year); the presence of PVT was not significantly associated with overall mortality for the cirrhotic patients undergoing surgical or interventional shunts. 33 Notably, Perarnau et al 34 showed that cumulative survival rates were not significantly different between TIPSS-treated cirrhotic patients with and without PVT (1 year: 80% vs 84%; 2 years: 72% vs 70%; and 4 years: 55% vs 52%; Figure 3. A, Cumulative variceal rebleeding rates in patients with and without PVT after transjugular intrahepatic portosystemic shunt (P ¼ .023, by log-rank test).…”
Section: Discussionmentioning
confidence: 97%
“…Portal vein thrombosis (PVT) negatively influences the outcomes of cirrhotic patients (1)(2)(3)(4)(5)(6). However, no consensus regarding the treatment strategy of PVT in cirrhosis is well established (7,8).…”
mentioning
confidence: 99%